Structure and analgesic properties of layered double hydroxides intercalated with low amounts of ibuprofen. Issue 6 (25th March 2017) - Sousa, Robson; Jouin, Jenny; Masson, Olivier; Remondiere, Fabien; Lemarchand, Alex; Colas, Maggy; Thomas, Philippe; Lameira, Jerônimo; Bastos, Gilmara N. T.; Lima, Anderson B.; Nascimento, José L. M.; Anicete‐Santos, Marcos; et al.
Abstract: Ibuprofen‐intercalated layered double hydroxides (LDH‐IBU) have been successfully synthesized via a coprecipitation method with a nominal [Al 3+ ]/[Mg 2+ ] ratio of 0.5 and a variable molar IBU/([Al 3+ ]+[Mg 2+ ]) ratio of 0, 0.15, 0.18, 0.24, 0.36, and 0.72. After an accurate determination of the composition, the nature of the intercalated species and the effective intercalation yield from NO 3 − to IBU, it is shown that the synthesis route used allows a good control of the quantity of intercalated IBU within the LDH framework. This results in different samples with full or partial IBU intercalation in the interlayer space in exchange of nitrate anions. The analysis of the X‐ray diffraction basal reflections reveals that the intercalation of IBU in the framework only increases the basal distances with no alteration of the brucite‐type layers. Also, a computational study used to model the positions and shapes of the basal reflections showed that the structure of the nonfully intercalated compounds follows a random interstratification scheme. Finally, three samples ranging from slightly to fully IBU‐intercalated galleries were selected for preliminary in vivo assays. These tests showed a strong tendency that after 24 hours the low yield of IBU‐intercalated compounds are almost as efficient as the fully intercalated sample.